The Problem of Religious Language ‘Look at it this way’ (Wittgenstein)* - Marshall, Graeme (Sophia, 2012)
This essay is critical of some of the attempts made to solve problems of meaning in religious languages, but remains open-minded about them and accepts the Wittgensteinian invitation to look at their dissolution by way of the experiences of meaning and the aspects of language on which they rely. I have argued that there were and are no lasting problems with religious language per se and that the force and meaning of what is said in using religious language over time and circumstance may vary even to the point of having to retrieve concepts feared lost. We may in addition give ourselves our own personal interpretations by which we want to live and discuss with those in our space of reasons where good conversation is ever an inexhaustible provision on the way to enlightened understanding. Furthermore, we are not merely passive recipients of the meanings and significance of the languages we know. Finally, much of the meaning of religious language comes with the experience of being struck again by what has always been loved and by new aspects of, or different ways of taking, what is presented.